PENGARUH PENAMBAHAN PROBIOTIK PADA PAKAN TERHADAP PERTUMBUHAN DAN KONVERSI PAKANIKAN PATIN (Pangasius hypopthalmus) Effect of Probiotic in addition on Growth and Feed Conversion Ratio of Catfish (Pangasius hypopthalmus). - Abdillah Parinduri; Syammaun Usman; Desrita Desrita (AQUACOASTMARINE, 2017)
Catfish is consumption fish , with a chewy meat structure, easily separated with its thorns and low calorie content, 120 calorie each 3.5 ounce. Catfish are also used as ornamental fish in the aquarium with a shiny silver body color, as well as agile body movements make catfish widely favored ornamental fish lovers. The purpose of this study was to determine effect of probiotic in addition on growth and feed conversion ratio of catfish. This study used a Completely Randomized Design (CRD) with four treatments, namely, P0 (without the addition / control), P1( probiotic addition 1 g / kg), P2 (probiotic addition 2 g / kg), P3 (probiotic addition 3 g / kg ). The treatment P1 provides a significant influence on weight gain, but no significant effect on the length catfish. The treatment P1 is the best dose for the growth catfish with growth 8,54 cm long value and weight value 7,56 g and feed conversion ratio 0,82.Keyword: Catfish, Growth, Probiotics. FCR